Autonomous notification and situation reporting for flood disaster management - Ku-Mahamud, Ku Ruhana; Md Norwawi, Norita; Katuk, Norliza; Deris, Safaai (Canadian Center of Science and Education, 2008)
Failed management in emergency response effort due to inefficient and ineffective operation influences the adoption of information and communication technology specifically the Internet technology and World Wide Web. Timeliness,rapid response and efficient information dissemination are crucial in emergency management. This paper proposes a software design architecture taking advantage of the intelligent agent technology to facilitate autonomous notification and auto generates situation report. The adoption of agent technology has made it possible to produce scheduled report with standardized format that can reduce duplications and redundancies of information.